2022
DOI: 10.1002/brb3.2597
|View full text |Cite
|
Sign up to set email alerts
|

Built to last: Theta and delta changes in resting‐state EEG activity after regulating emotions

Abstract: Background : Over the past years, electroencephalography (EEG) studies focused on task‐related activity to characterize cortical responses associated with emotion regulation (ER), without exploring the possibility that regulating emotions can leave a trace in the brain by affecting its oscillatory activity. Demonstrating whether the effect of regulation alters the brain activity after the session and whether this reflects an increased cognitive regulatory ability has great relevance. Methods : To address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…We recorded rs-EEG data for each participant for six minutes. The acquisition duration is in line with previous rs-EEG studies ( Babiloni et al., 2023 ; Lapomarda, Valer, Job, & Grecucci, 2022 ; Sun et al., 2019 ). In addition, because opening and closing the eyes reflect different resting states ( Barry, Clarke, Johnstone, Magee, & Rushby, 2007 ), we included both opened and closed eyes to detect an entire resting state.…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…We recorded rs-EEG data for each participant for six minutes. The acquisition duration is in line with previous rs-EEG studies ( Babiloni et al., 2023 ; Lapomarda, Valer, Job, & Grecucci, 2022 ; Sun et al., 2019 ). In addition, because opening and closing the eyes reflect different resting states ( Barry, Clarke, Johnstone, Magee, & Rushby, 2007 ), we included both opened and closed eyes to detect an entire resting state.…”
Section: Methodssupporting
confidence: 62%
“…Meanwhile, we found a similar scale-free effect at the delta band. Although few studies reported the association between topological deviations in the delta band and emotions, delta frequency has been shown to play an important role in emotion regulation ( Jiang et al., 2022 ; Lapomarda et al., 2022 ). Additionally, similar emotional profiles were associated with similar delta-band activities over the prefrontal and temporoparietal regions ( Hu, Wang, & Zhang, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For our study, we selected 3 out of 21 subjects in our dataset based on similarities in EEG patterns during initial EEG channel visualizations, reducing intersubject variability; 25 out of 31 EEG channels for each subject were used and we focused on the delta, theta and alpha bands for their role in emotional processing, meditation/relaxed physical states and music cognition and emotion, respectively 60,[62][63][64] .…”
Section: Resultsmentioning
confidence: 99%
“…Beta rhythm is also generally related to high-level cognitive processes and attention focusing, and high stress causes increased amplitudes in this band. The low-frequency Delta and Theta bands are often seen as markers of the internal concentration of attention when processing information and of the emotional regulation when perceiving various emotion-causing stimuli [ 47 , 48 ]. Therefore, in our experimental study we explore and interpret the EEG signals in each band and relate them to the other variables considered in the study.…”
Section: Methods and Related Workmentioning
confidence: 99%